Fluorous-tagged bortezomib supramolecular nanomedicine for cancer therapy - Changping Wang; Xin Gao; Zhan Li; Xinyu Wang; Yiwen Li; Yiyun Cheng (Supramolecular Materials)
Lipidation is a well-established post-translational modification strategy to modulate the structure and function of proteins and peptides. Lipids can improve the overall or local hydrophobicity of the biomolecule, boosting its affinity with the cell membranes. Lipidation, despite its great potential, remains an underutilized technique for translating bioactive molecules into the clinic. Herein, we have optimized the lipidation strategy by involving the fluorous lipidation combined with supramolecular engineering, which can be facilely achieved by grafting an anticancer peptide drug (bortezomib, BTZ) with a series of fluorous lipids bearing a catechol moiety via the dynamic catechol-boronate ester bond. Compared with BTZ, the fluorous-tagged BTZ nanomedicine exhibited an on-demand and traceless release behavior, and enhanced therapeutic effect and biocompatibility. More importantly, the fluorous tag could improve the serum stability of the supramolecular nanomedicine, which allowed efficient in vivo utilization of BTZ to kill cancer cells. This work introduces a novel lipidation strategy for bioactive peptides via the integration of fluorination chemistry and supramolecular engineering strategies.